Math anxiety, learning engagement and perceived usefulness of technology as predictors to mathematics performance of students - Eugine Bahian Dodongan (International Journal of Trends in Mathematics Education Research, 2022)
The focus of this research was to verify if there was a link among anxiety toward mathematics, learning engagement, and their perception of technology's usefulness in mathematics. This ex-post research looked into the relationship and predictive degree of students' math anxiety, learning engagement, and perceived usefulness of technology to their mathematics achievement. Students' math anxiety and perceived usefulness of technology were found to be high in the study, whereas student engagement was found to be low and level of students' performance in mathematics was also high. Both math anxiety and students' perceptions of the utility of technology in learning have a significant impact on students' mathematics performance, but not on their engagement. The findings showed the importance of a high level of anxiety in improving student math performance. Additionally, math anxiety and the perceived usefulness of technology were discovered to be predictors of student mathematics performance. The findings suggest that anxiety, engagement, and perceptions of technology's usefulness should all be considered when improving students' general mathematics performance.